2009
DOI: 10.1096/fj.08-114421
|View full text |Cite
|
Sign up to set email alerts
|

Cutinase‐like proteins of Mycobacterium tuberculosis : characterization of their variable enzymatic functions and active site identification

Abstract: Discovery and characterization of novel secreted enzymes of Mycobacterium tuberculosis are important for understanding the pathogenesis of one of the most important human bacterial pathogens. The proteome of M. tuberculosis contains over 400 potentially secreted proteins, the majority of which are uncharacterized. A family of seven cutinase-like proteins (CULPs) was identified by bioinformatic analysis, expressed and purified from Escherichia coli, and characterized in terms of their enzymatic activities. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
88
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 56 publications
5
88
0
Order By: Relevance
“…2D). Seven cutinase-like proteins, with esterase activities in some of them, have been described in M. tuberculosis (42,51), and we suggest that one or more of these behaves similarly to Msmeg_1529, although none has yet been shown to cleave either TDM or mAGP. Rv3452, designated Culp4, is the closest relative of Msmeg_1529, has a putative signal peptide, and has been reported to be cell wallassociated (52).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…2D). Seven cutinase-like proteins, with esterase activities in some of them, have been described in M. tuberculosis (42,51), and we suggest that one or more of these behaves similarly to Msmeg_1529, although none has yet been shown to cleave either TDM or mAGP. Rv3452, designated Culp4, is the closest relative of Msmeg_1529, has a putative signal peptide, and has been reported to be cell wallassociated (52).…”
Section: Discussionmentioning
confidence: 74%
“…These two molecules are, therefore, the major candidates for substrates for the generation of FM, although cellular esterases that hydrolyze these have not been described. We note though that the mycobacteriophage lysin B enzyme has recently been shown to cleave mAGP (41), and there are several mycobacterial cutinase-like proteins for which lipolytic activity has been reported (42).…”
Section: Resultsmentioning
confidence: 82%
“…The putative product of Rv3802c has a predicted signal sequence that contains a possible transmembrane domain, and it has been expressed to assess immunological responses (13) and enzymatic activities. The enzyme is one of seven cutinaselike proteins in M. tuberculosis and is retained in the cell wall, following translocation across the cell membrane (14). Previous studies have shown it to have phospholipase A and thioesterase activities (12), consistent with a role in mycolic acid biosynthesis, and significant lipase activity completely dependent on its Ser-Asp-His catalytic triad (14).…”
mentioning
confidence: 99%
“…The enzyme is one of seven cutinaselike proteins in M. tuberculosis and is retained in the cell wall, following translocation across the cell membrane (14). Previous studies have shown it to have phospholipase A and thioesterase activities (12), consistent with a role in mycolic acid biosynthesis, and significant lipase activity completely dependent on its Ser-Asp-His catalytic triad (14). A very recent study has suggested a role for Rv3802c in regulation of outer lipid composition in response to stress because the induction of the Corynebacterium glutamicum ortholog triggered an increase in mycolic acid biosynthesis as part of an outer membrane remodeling response to heat stress (15).…”
mentioning
confidence: 99%
“…The therapeutic utility of the identified potential multi-target inhibitors against Rv0183 and Rv3802c could be validated by the TB research community. Knowledge about Rv3802c of M. tuberculosis can open a new horizon towards understanding cutinases and PE-PPE enzymes of the pathogen as well as for tuberculosis therapeutics [16,17].…”
Section: Discussionmentioning
confidence: 99%